Microtubules guide root hair tip growth - Sieberer, Björn J (The New phytologist, 2005)
The ability to establish cell polarity is crucial to form and function of an individual cell. Polarity underlies critical processes during cell development, such as cell growth, cell division, cell differentiation and cell signalling. Interphase cytoplasmic microtubules in tip-growing fission yeast cells have been shown to play a particularly important role in regulating cell polarity. By placing proteins that serve as spatial cues in the cell cortex of the expanding tip, microtubules determine the site where exocytosis, and therefore growth, takes place. Transport and the targeting of exocytotic vesicles to the very tip depend on the actin cytoskeleton. Recently, endoplasmic microtubules have been identified in tip-growing root hairs, which are an experimental system for plant cell growth. Here, we review the data that demonstrate involvement of microtubules in hair elongation and polarity of the model plants Medicago truncatula and Arabidopsis thaliana. Differences and similarities between the microtubule organization and function in these two species are discussed and we compare the observations in root hairs with the microtubule-based polarity mechanism in fission yeast